2015
DOI: 10.2172/1188908
|View full text |Cite
|
Sign up to set email alerts
|

Responder Technology Alert (February 2015)

Abstract: PNNL RTA Monthly Report Sensors 2.12 also required by sports and fitness applications that need to differentiate between the different types of 'steps' a wearer might be taking and the corresponding calorie 'burn rate'." Status: Soon to be released

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It revealed that there is a need for devices that provide information about and for first responders in real time. Another report by the U.S. Pacific Northwest National Laboratory and the First Responder Technology Alliance of the U.S. Department of Homeland Security (DHS) [9] reviewed the advanced technologies for first responders such as physiological and biological sensors, heads-up and body-worn visual displays, body-worn sensors, smart glasses, self-powering technologies, hands-free ergonomically optimized communication systems, body-worn cameras, and breathing apparatus. Our brief followup audit of these and other works identifies the main directions of the R&D in the area of emergency management:…”
Section: Related Work and Randd Landscapementioning
confidence: 99%
See 3 more Smart Citations
“…It revealed that there is a need for devices that provide information about and for first responders in real time. Another report by the U.S. Pacific Northwest National Laboratory and the First Responder Technology Alliance of the U.S. Department of Homeland Security (DHS) [9] reviewed the advanced technologies for first responders such as physiological and biological sensors, heads-up and body-worn visual displays, body-worn sensors, smart glasses, self-powering technologies, hands-free ergonomically optimized communication systems, body-worn cameras, and breathing apparatus. Our brief followup audit of these and other works identifies the main directions of the R&D in the area of emergency management:…”
Section: Related Work and Randd Landscapementioning
confidence: 99%
“…In our study, we adopted and extended the SmartHub platform [7] combined with updated specifications of WiLIFE [8] and advances in responder technology components [1,9,10,12,21,24,57].…”
Section: Composite Ngfr Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the HWD used in both experiments was the monocular and opaque Vuzix M100 HWD. New HWDs are being rapidly developed with new technology and features (Upton & Stein, 2015). Just as it is important for the current findings to be tested in high-fidelity clinical environments and with clinician participants, so is it important to perform tests of different devices such as binocular see-through augmented reality glasses.…”
Section: Limitations and Future Researchmentioning
confidence: 99%